2022
DOI: 10.1136/jitc-2022-005577
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive single-KIR+NKG2C+NK cells expanded from select superdonors show potent missing-self reactivity and efficiently control HLA-mismatched acute myeloid leukemia

Abstract: BackgroundNatural killer (NK) cells hold great promise as a source for allogeneic cell therapy against hematological malignancies, including acute myeloid leukemia (AML). Current treatments are hampered by variability in NK cell subset responses, a limitation which could be circumvented by specific expansion of highly potent single killer immunoglobulin-like receptor (KIR)+NKG2C+adaptive NK cells to maximize missing-self reactivity.MethodsWe developed a GMP-compliant protocol to expand adaptive NK cells from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…If KIR/HLA genetics are primarily relevant to understanding if a haploidentical donor can be NK alloreactive, the actual frequency of this subset in the total NK cell repertoire should be evaluated by phenotypic and/or functional assays. These studies allow the choice of the most suitable donor, including the identification of “superdonors” ( 59 ), whose NK repertoire reveals the highest frequency of alloreactive NK cells, and also the quantification of the “functional NK cell dose” to be infused into the patient. In conclusion, the systematic parallel study of NK alloreactivity and the critical view of the two approaches add new insights into the criteria for donor selection in the haploidentical setting.…”
Section: Discussionmentioning
confidence: 99%
“…If KIR/HLA genetics are primarily relevant to understanding if a haploidentical donor can be NK alloreactive, the actual frequency of this subset in the total NK cell repertoire should be evaluated by phenotypic and/or functional assays. These studies allow the choice of the most suitable donor, including the identification of “superdonors” ( 59 ), whose NK repertoire reveals the highest frequency of alloreactive NK cells, and also the quantification of the “functional NK cell dose” to be infused into the patient. In conclusion, the systematic parallel study of NK alloreactivity and the critical view of the two approaches add new insights into the criteria for donor selection in the haploidentical setting.…”
Section: Discussionmentioning
confidence: 99%
“… 81 Moreover, a recent report demonstrated the use of a GMP-compliant expansion protocol that confers NK cells’ sustainable adaptive features with robust tumor-killing capacity. 82 Gang et al also demonstrated CAR-transduced memory-like NK cells had better anti-tumoral responses compared with conventional CAR-NK cells in the treatment of such NK-resistant lymphoma. 83 Additionally, the targeting of cytokine-inducible SH2-containing protein (CIS) which is a potent negative regulator of IL-15 signaling pathway, would also enhance NK cell functions.…”
Section: Nks—‘off-the-shelf’ Therapeutics For Cancer Treatmentmentioning
confidence: 99%
“…Recapitulating the HCMVinduced expansion of NKG2A − NKG2C + NK cells to overcome viral immune evasion and translating this naturally occurring process into a tool for therapeutic application is an intriguing approach. Leveraging the inherent response pattern during coculture with HLA-E-expressing feeder cells allows for the selective expansion of NKG2A − NKG2C + NK cells in vitro [29][30][31][32]. These NKG2A − NKG2C + NK-cell products combine the absence of inhibition through the lack of NKG2A with robust activation through the presence of NKG2C and thus represent optimal candidates for the treatment of tumors enriched for HLA-E expression.…”
Section: Strategies For Overcoming Immune Evasion Through the Hla-e-n...mentioning
confidence: 99%
“…Prevention of binding between NKG2A and HLA-E to avoid inhibition of infused cells [26,27] Infusion of NK cells with blocked NKG2A expression Prevention of binding between NKG2A and HLA-E to avoid inhibition of infused cells [28] Infusion of NKG2A − NKG2C + NK cells Selective growth of NKG2A − NKG2C + NK cells in vitro to preclude NKG2A-mediated inhibition and simultaneously enables NKG2C-driven activation upon binding to HLA-E [32] Potential modulation of the tumor HLA-E peptidome Window of opportunity to adjust the pool of peptides presented on HLA-E with the goal to interfere with the binding between HLA-E/peptide complexes and NKG2A…”
Section: Evasion Category Therapeutic Strategy Intended Effect Refere...mentioning
confidence: 99%